(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
An old short saying "United we stand, divide we fall" works today to help small investors by investing in mutual funds as it help them to stand united, reducing risk by diversification and to provide higher returns in comparison to traditional non risky investment avenues. In the current era a retail investor has many options available to invest his money to get future return according to their goals and risk bearing capacity which varies from old traditional schemes to newly launched various schemes. It has been found from the previous past studies that small and medium retail investors are still investing majority of their surplus in banks, post office and other traditional investment options which is not providing them real higher returns. Some of them are taking risk and investing in risky securities but because of less understanding of market they got losses from direct market investments. As a solution Mutual Fund is the best investment option which is available to a retail investor which provides higher return then traditional investment options with availability of multiple level of diversification and managed by professional expert fund managers which help in reducing risk too. It has been seen that mutual funds hove outperformed in the long run by giving persistent higher returns but still captured very less percentage of the market due to lack of awareness and familiarity. The objective to this paper is to explore how mutual fund is a better investment option in current era and understanding of Investor’s perception towards Mutual Fund investments other than Non Risky Investment avenues. Primary data from structured questionnaire and secondary data from various sources have been collected and used in this research. The study further help in understanding the comparison between mutual fund and various other investments. The study reveals that those retail investor who have invested in mutual funds are satisfied and get good returns as compared to other traditional investment options but still there is a requirement of more understanding. The paper suggests that by spreading awareness and making digital availability of mutual fund investment can help in tapping more investors so as to provide higher return and fulfill their objectives and setting the mutual fund industry growth path.